Korelasi Antara Kepercayaan Diri Dengan Aktualisasi Diri Siswa SMK YATPI Godong - Roni Bagus Setiyawan; Eka Sari Setianingsih; Mujiono Mujiono (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2023)
The need for self-actualization is achieved to maximize all abilities and potential. The purpose of this study is to determine the relationship between self-confidence and self-actualization. In this study, researchers used a quantitative approach with a correlational type of research. Correlation research is research that aims to determine the relationship between two or more variables as they are without treatment. The population in this study were students of Class X at SMK YATPI Godong, Grobogan Regency. The sample used was 199 students from class X at SMK YATPI Godong, Grobogan Regency. The results of this study can be concluded that there is a significant correlation between self-confidence and self-actualization of YATPI Godong Vocational High School students. and able to optimize the strengths or potential that students have.